Manajemen Perkantoran Modern Di Era Digitalisasi: Suatu Tinjauan Literatur - Victorio Fernando Nahuway (P3M Politeknik Negeri Ambon, 2024)
Digitalization has significantly impacted office management, bringing automation to routine tasks like document handling, employee communication, and collaboration. Technologies such as project management software and cloud computing have enhanced real-time teamwork and accessibility, especially for remote work. Despite these advantages, challenges like data security and adapting to new technologies persist. Digital transformation isn't just about adopting technology but also involves shifts in work culture and human resource management. To fully benefit, companies must invest in technology, provide employee training, and prioritize digital security. Clear remote work policies are also essential to maintain productivity. Future research should focus on technology, organizational culture, human resources, and data security. Keywords: Cloud computing, Digitalization, Internet of Things, Big Data